Malaysian academicians perspectives on continuous professional development of academics in Malaysian public universities - Asimiran, Soaib; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Public universities in Malaysia are expected to produce graduates who are not only employable, but must also be capable to contribute to the development of the nation and to fulfil national aspirations which ultimately make the Malaysian public universities remain competitive in the QS World Ranking of Universities. One of the critical factors that would enable this is by supporting the continuous professional development (CPD) for the academics so that they would be able to enhance their quality of teaching, research and consultancy services as their core duties. This study addresses the perspectives of the Malaysian academicians in public universities with regard to the implementation of continuous professional development initiatives taken by the respected public universities. Employing the qualitative approach, we analysed the perspectives of the academicians from public universities on the issues and challenges as well as institutional support given to them related to continuous professional development of the academicians. Data are drawn from interviews with several academicians as well as analysis of relevant documents. Findings indicated that the academicians have specific and diverse needs for CPD in order to enhance the quality of their teaching, research and consultancy services. They concurred that the universities have provided relevant support for CPD especially to the young academicians. There are areas in which support was particularly strong and other areas which the universities are constraint due to reduction of annual budget. Various issues and challenges with regard to institutional governance as the framework and policies are being strengthened to equip the academicians with the Industrial Revolution 4.0 (IR 4.0) requirements so as to make them remain relevant, referred and respected in their functions.